2006
DOI: 10.1002/cncr.21650
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent endometrial carcinoma in women with a biopsy diagnosis of atypical endometrial hyperplasia

Abstract: BACKGROUNDAdenocarcinoma of the endometrium is the most common gynecologic malignancy in the United States, accounting for approximately 36,000 diagnoses of invasive carcinoma annually. The most common histologic type, endometrioid adenocarcinoma (EC), accounts for 75–80% of patients. The objective of this work was to estimate the prevalence of concurrent carcinoma in women with a biopsy diagnosis of the precursor lesion, atypical endometrial hyperplasia (AEH).METHODSThis prospective cohort study included wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
321
1
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 540 publications
(352 citation statements)
references
References 23 publications
17
321
1
13
Order By: Relevance
“…6,7,11,13,14 We found that the presence of AIS in complex atypical endometrial hyperplasia patients was associated with significantly greater likelihood of finding endometrial adenocarcinoma and myoinvasive endometrial adenocarcinoma on subsequent hysterectomy. Approximately two-thirds of patients with AIS in endometrial curettage/biopsy have endometrial adenocarcinoma on subsequent hysterectomy vs about a quarter of those that lack AIS.…”
Section: Discussionmentioning
confidence: 66%
“…6,7,11,13,14 We found that the presence of AIS in complex atypical endometrial hyperplasia patients was associated with significantly greater likelihood of finding endometrial adenocarcinoma and myoinvasive endometrial adenocarcinoma on subsequent hysterectomy. Approximately two-thirds of patients with AIS in endometrial curettage/biopsy have endometrial adenocarcinoma on subsequent hysterectomy vs about a quarter of those that lack AIS.…”
Section: Discussionmentioning
confidence: 66%
“…This statistic was significantly higher than the traditionally accepted rate of 25% 6 and consistent with other more recent reviews. [7][8][9][10] Sixteen percent of our patients with concurrent EC were also found to have significant-risk cancers. We interpreted these results to mean that managing all patients who have a preoperative diagnosis of AEH with routine HBSO may be suboptimal.…”
Section: Discussionmentioning
confidence: 77%
“…Although it seems widely accepted that 23% to 25% of patients with AEH will progress to cancer, 1,2 the frequency and significance of concurrent EC remains controversial. [3][4][5][6][7][8][9][10] The traditional view has been that concurrent EC is acceptably infrequent and of low importance in patients with preoperative AEH. [3][4][5] In 1993, Janicek et al summarized the results of six studies in which 122 of 463 patients with AEH (26%) were found to have concurrent EC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations